2009
DOI: 10.2174/092986709789878274
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Lipoic Acid Conjugates

Abstract: Several hundreds of studies published the last decade have reported that alpha-lipoic acid (LA) possess the potential to intervene in various therapeutically interesting pathways. However, it should be noted that LA reportedly exerts most of its effects at high micromolar concentrations; that amides of LA exhibit higher biological activity than the parent compound; and that molecular combinations (hybrids) obtained by coupling LA with an amino-substituted bioactive moiety, possess multifunctional activity. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Improved solubility promotes more uniform formulation which is important for consistent cholesterol reducing effects, even though free PS and PS es- Conjugates of LA have been synthesised for their anticipated dual and/or synergistic health benefi ts. In addition, it has been suggested that LA conjugates may possess its therapeutic effect at lower concentrations than required for LA alone [Koufaki et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved solubility promotes more uniform formulation which is important for consistent cholesterol reducing effects, even though free PS and PS es- Conjugates of LA have been synthesised for their anticipated dual and/or synergistic health benefi ts. In addition, it has been suggested that LA conjugates may possess its therapeutic effect at lower concentrations than required for LA alone [Koufaki et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of hybrid molecules is a common approach to create effi cient and/or synergistic effects either on single or dual targets. It was also suggested that multifunctional LA conjugates may bring their therapeutic effects at lower concentrations compared to the LA as a single molecule [Koufaki et al, 2009;Melagraki et al, 2009]. The main objectives of this study were to synthesize LA and DHLA conjugates of PS in a mixture (β-sito-, stigma-, campe-, and brassicasterol), yielding phytosterol lipoate (PSLA) and phytosterol dihydrolipoate (PSDHLA), respectively, and to verify them by NMR and HPLC-MS. To our knowledge, no research paper has been published on these conjugates .…”
Section: Introductionmentioning
confidence: 99%
“…26 Thus, LA is a good prototype to design new hybrids to combat AD, and previously developed LA hybrids maintained the antioxidant activity and showed other beneficial activities such as inhibition of AChE and BuChE as well as neuroprotective and anti-inflammatory activity. 27,28 In 2005, Rosini et al 29 reported the synthesis of lipocrine, an LA-tacrine hybrid, which further inspired the development of other hybrids featuring an LA fragment connected with N 1 -ethyl-N 1 -(2-methoxy-benzyl)-hexane-1,6-diamine moiety or with rivastigmine. 26 Although there are works involving the hybridization of the benzyl-piperidine moiety of donepezil with LA, to our knowledge, there is no report on the hybridization of the indanone-piperidine moiety with LA.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 In 2005, Rosini et al 29 reported the synthesis of lipocrine, an LA-tacrine hybrid, which further inspired the development of other hybrids featuring an LA fragment connected with N 1 -ethyl-N 1 -(2-methoxy-benzyl)-hexane-1,6-diamine moiety or with rivastigmine.…”
mentioning
confidence: 99%
“…Many studies paid attention to sulfide and disulfide moiety compounds, with lipoic acid being one of the most useful compounds for gold surface functionalization [2,3]. Lipoic acid was widely used because its alkyl chain length and disulfide attachment c 2015 Vietnam Academy of Science and Technology to gold surface results in the enhanced stability of the monolayer [4,5]. The functionalization of the self-assembled monolayer after activation with a mixture of dicyclohexyl carbodiimide and N-hydroxysuccinimide is a well established method for the further functionalization of biosensors [6].…”
Section: Introductionmentioning
confidence: 99%